PDM Klein-Gordon particles in Godel-type Som-Raychaudhuri cosmic string spacetime background - Mustafa, Omar (Springer Heidelberg, 2023)
In Godel-type Som-Raychaudhuri (SR) cosmic string spacetime background, we revisit Klein-Gordon (KG) oscillators and report their exact solutions for positive/negative vorticity parameter, S2 = +/-|S2|. Consequently, a new type of degeneracy associated with a rotating Godel universe is found feasible. We also introduce KG oscillators in a pseudo-Godel SR-type spacetime that admit invariance and isospectrality with those in Godel SR-type spacetime background. We introduce position-dependent mass (PDM) settings to KG particles in four-vector and scalar Lorentz potentials in magnetic field in the Godel SR-type spacetime background. Four illustrative examples of fundamental nature are discussed, and their exact or conditionally exact solvability are reported. They are, a PDM KG-Coulombic particle in four-vector and scalar Coulombic Lorentz potentials in magnetic field, a PDM KG-Coulombic particle in four-vector and scalar Coulombic Lorentz potentials in magnetic field at zero vorticity, a PDM KG-Coulombic particle in equally mixed four-vector and scalar Coulombic Lorentz potentials in magnetic field, and a quasi-free PDM KG oscillator.
Keywords: Position-Dependent Mass; Gravitational-Field; Oscillator; Dirac; Expansion; Equation; State